Middleware 2009 c - Bacon, Jean M.; Cooper, Brian F.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2009)
This edition marks the tenth Middleware conference. The ?rst conference was held in the Lake District of England in 1998, and its genesis re?ected a growing realization that middleware systems were a unique breed of distributed system requiring their own rigorous research and evaluation. Distributed systems had been around for decades, and the Middleware conference itself resulted from the combination of three previous conferences. But the attempt to build common platforms for many di?erent applications requireda unique combinationofhi- level abstraction and low-level optimization, and presented challenges di?erent from building a monolithic distributed system. Since that ?rst conference, the notion of what constitutes (3z(Bmiddleware(3y (Bhas changed somewhat, and the focus of research papers has changed with it. The ?rst edition focused heavily on distributed objects as a metaphor for building systems, including six papers with (3z(BCORBA(3y (Bor (3z(BORB(3y (Bin the title. In f- lowing years, the conference broadened to cover publish/subscribe messaging, peer-to-peer systems, distributed databases, Web services, and automated m- agement, among other topics. Innovative techniques and architectures surfaced in workshops, and expanded to become themes of the main conference, while changes in the industry and advances in other research areas helped to shape research agendas. This tenth edition includes papers on next-generation pl- forms (such as stream systems, pervasive systems and cloud systems), managing enterprise data centers, and platforms for building other platforms, among o- ers.s
Communications I (Protocols) -- MANETKit: Supporting the Dynamic Deployment and Reconfiguration of Ad-Hoc Routing Protocols -- Automatic Generation of Network Protocol Gateways -- Heterogeneous Gossip -- Communications II (Optimization) -- CCD: Efficient Customized Content Dissemination in Distributed Publish/Subscribe -- Calling the Cloud: Enabling Mobile Phones as Interfaces to Cloud Applications -- Efficient Locally Trackable Deduplication in Replicated Systems -- Service Component Composition/Adaptation -- QoS-Aware Service Composition in Dynamic Service Oriented Environments -- Self-adapting Service Level in Java Enterprise Edition -- A Cost-Sensitive Adaptation Engine for Server Consolidation of Multitier Applications -- Monitoring -- Rhizoma: A Runtime for Self-deploying, Self-managing Overlays -- How to Keep Your Head above Water While Detecting Errors -- PAQ: Persistent Adaptive Query Middleware for Dynamic Environments -- Pervasive -- Middleware for Pervasive Spaces: Balancing Privacy and Utility -- Achieving Coordination through Dynamic Construction of Open Workflows -- Power Aware Management Middleware for Multiple Radio Interfaces -- Stream Processing -- COLA: Optimizing Stream Processing Applications via Graph Partitioning -- Persistent Temporal Streams -- Failure Resilience -- Why Do Upgrades Fail and What Can We Do about It? -- DR-OSGi: Hardening Distributed Components with Network Volatility Resiliency -- Support for Testing -- Automatic Stress Testing of Multi-tier Systems by Dynamic Bottleneck Switch Generation -- DSF: A Common Platform for Distributed Systems Research and Development.
Keywords: Computer science; Computer organization; Computer communication systems; Software engineering; Operating systems (Computers).; Computers; Computer Science; Operating Systems; Computer Communication Networks; Theory of Computation; Software Engineering; Software Engineering/Programming and Operating Systems; Computer Systems Organization and Communication Networks; Electronic books